An afternoon snack of berries reduces subsequent energy intake compared to an isoenergetic confectionary snack. (1st December 2015) - James, Lewis J.; Funnell, Mark P.; Milner, Samantha
Abstract: Observational studies suggest that increased fruit and vegetable consumption can contribute to weight maintenance and facilitate weight loss when substituted for other energy dense foods. Therefore, the purpose of the present study was to assess the effect of berries on acute appetite and energy intake. Twelve unrestrained pre-menopausal women (age 21 ± 2 y; BMI 26.6 ± 2.6 kg m −2 ; body fat 23 ± 3%) completed a familiarisation trial and two randomised experimental trials. Subjects arrived in the evening (∼5pm) and consumed an isoenergetic snack (65 kcal) of mixed berries (BERRY) or confectionary sweets (CONF). Sixty min later, subjects consumed a homogenous pasta test meal until voluntary satiation, and energy intake was quantified. Subjective appetite (hunger, fullness, desire to eat and prospective food consumption) was assessed throughout trials, and for 120 min after the test meal. Energy intake was less ( P <0.001) after consumption of the BERRY snack (691 ± 146 kcal) than after the CONF snack (824 ± 172 kcal); whilst water consumption was similar ( P =0.925). There were no trial ( P >0.095) or interaction ( P >0.351) effects for any subjective appetite ratings. Time taken to eat the BERRY snack (4.05 ± 1.12 min) was greater ( P <0.001) than the CONF snack (0.93 ± 0.33 min). This study demonstrates that substituting an afternoon confectionary snack with mixed berries decreased subsequent energy intake at dinner, but did not affect subjective appetite. This dietary strategy could represent a simple method for reducing daily energy intake and aiding weight management. Highlights: Appetite and energy intake responses following two afternoon snacks were compared. Snacks were mixed berries or confectionary and were matched for energy content. Energy intake was lower after the mixed berries compared to the confectionary. There was no difference between trials for any measure of subjective appetite.